2008
DOI: 10.1073/pnas.0707025105
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal adaptation to environmental stress links resistance to proteotoxicity with longevity in Caenorhabditis elegans

Abstract: The burden of protein misfolding is believed to contribute to aging. However, the links between adaptations to conditions associated with protein misfolding and resistance to the time-dependent attrition of cellular function remain poorly understood. We report that worms lacking aip-1, a homologue of mammalian AIRAP (arsenic-inducible proteasomal 19S regulatory particle-associated protein), are not only impaired in their ability to resist exposure to arsenite but also exhibit shortened lifespan and hypersensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 27 publications
3
93
1
Order By: Relevance
“…aip-1/ AIRAP binds to the 19S increasing proteasome activity and clearance of damaged proteins 181 . Notably, aip-1/AIRAP ameliorates Ab and polyQ toxicity 182,183 . Moreover, skn-1 and its mammalian orthologues Nrf1 and Nrf2 upregulate the expression of proteasomal genes in response to proteasome inhibition and oxidative stress 39 .…”
Section: Loss Of Clearance Mechanisms As a Determinant Of Ageingmentioning
confidence: 99%
“…aip-1/ AIRAP binds to the 19S increasing proteasome activity and clearance of damaged proteins 181 . Notably, aip-1/AIRAP ameliorates Ab and polyQ toxicity 182,183 . Moreover, skn-1 and its mammalian orthologues Nrf1 and Nrf2 upregulate the expression of proteasomal genes in response to proteasome inhibition and oxidative stress 39 .…”
Section: Loss Of Clearance Mechanisms As a Determinant Of Ageingmentioning
confidence: 99%
“…2B). Moreover, previous studies had shown that AIRAP and AIRAPL, mammalian proteins related to Cuz1, can interact with the 26 S proteasome (40,41). To determine whether Cuz1 interacts with the yeast 26 S proteasome, we affinity purified 26 S proteasomes from yeast cells that expressed proteasomes with a FLAG epitope tag on either the Pre1 (␤4) subunit of the CP or the Rpn5 subunit of the RP.…”
Section: Cuz1 Binds To the Proteasome And Is Stimulated By Exposure Omentioning
confidence: 99%
“…Similarity between YNL155w and YOR052c is restricted to the Zf_AN1 domains (46% sequence identity over 32 residues). Two mammalian Zf_AN1 proteins, ZFAND2A/ AIRAP (zinc finger-AN1 domain/arsenite-inducible RNA-associated protein) and ZFAND2B/AIRAPL (AIRAP-like), were reported to bind the 26 S proteasome and may modulate its activity (40,41). The Caenorhabditis elegans ortholog of AIRAPL, AIP-1 has been genetically linked to proteotoxic stress resistance and increased longevity (40).…”
Section: Yeast Cuz1/ynl155w and Yor052c As Potential Ups Factors-mentioning
confidence: 99%
“…A subsequent bioinformatic search defined a minimal VIM consensus sequence and identified several additional VIM-containing proteins [63]. These include ANKZF1 (ANKyrin repeat and Zinc Finger domain-containing-1, also known as ZNF744 or Vms1), a protein that has been implicated in mitochondrial protein degradation [64]; the UBX protein UBXD1, involved in sorting of ubiquitylated cargo in the endocytic pathway [10]; AIRAPL (Arsenite Inducible RNA Associated Protein Like Protein, also known as ZFAND2B), an ER membrane-anchored protein which associates with and regulates the function of the 26S proteasome under arsenite stress [65]; SelS (also called VIMP, VCP-Interacting Membrane Protein), a protein involved in the recruitment of p97 to the ER membrane [66]; and the yeast protein Wss1, a metalloprotease involved in DNA-protein crosslink repair [67]. With the exception of SelS it was shown that these proteins interact via their VIM with p97 [63,64,[67][68][69].…”
Section: The Vcp-interacting Motifmentioning
confidence: 99%